Role of NOD-Like Receptors in a Miniature Pig Model of Diabetic Renal Injuries - Ren, Yi; Cui, Shaoyuan; Hong, Quan; Shen, Wanjun; Li, Qinggang; Wu, Lingling; Fu, Bo; Wang, Xu; Ma, Qian; Liu, Jiaona; Bai, Xueyuan; Chen, Xiangmei (Mediators of Inflammation, 2022)
Activation of NOD-like receptor (NLR) signaling pathway can promote downstream cytokine and proinflammatory cytokines release, and inflammation induced by excess nutrients leads to renal metabolic injury. How the NLRs influence metabolic progress and then lead to the renal injury remains poorly investigated. Compared with rodents, minipigs are more similar to humans and are more ideal animal models for human disease research. In this study, we established a diabetic minipig model through a high-sugar and high-fat diet combined with streptozotocin (STZ) injection. Blood biological markers and renal pathological markers, expression of NLRP subfamily members (NLRP1 and NLRP3) and their downstream cytokines (precursors of IL-1β and IL-18 and mature forms of IL-1β and IL-18), expression of NLRC subfamily members (NLRC1, NLRC2, and NLRC5) and their downstream nuclear factor-κB (NF-κB) signaling pathway molecules (IKKβ, IκBα, and NF-κB p65), and inflammatory cytokines (TNF-α and interleukin-6 (IL-6)) were systematically evaluated. The expression of NLRP3 and its downstream cytokine signaling molecules, the precursors of IL-1β and IL-18, and the mature forms of IL-1β and IL-18 was significantly upregulated. The expression levels of NLRC1, NLRC2, and NLRC5 and activation of the downstream NF-κB pathway molecules phospho-IKKβ, phospho-IκBα, NF-κB p65, and phospho-NF-κB p65 were significantly increased. The TNF-α and IL-6 levels were significantly increased in diabetic pig kidneys. The TGF-β/Smad signaling molecules, TGF-β and P-SMAD2/3, were also increased. These results suggested that the metabolic inflammation activated by NLRs might play an important role in diabetic renal injuries.